Serum Vitamin D levels at admission predict the length of intensive care unit stay but not in-hospital mortality of critically ill surgical patients - Nafiseh Alizadeh; Hossein Khalili; Mostafa Mohammadi; Alireza Abdollahi (Wolters Kluwer Medknow Publications, 2015)
Objective: There is few data regarding the correlation between serum Vitamin D level and unfavorable intensive care unit (ICU) outcome in postsurgical patients. In this study, correlation between serum 25(OH)D level and length of ICU stay and in-hospital mortality has been evaluated in critically ill surgical patients. Methods: Serum 25(OH)D has been evaluated in 70 surgical, critically ill patients. Demographic, laboratory, and clinical data of the patients were collected. Correlation between serum 25(OH) D level and duration of ICU stay and hospital mortality was evaluated using two-factor analysis of covariance. Multivariable Cox-regression analysis was used for adjusting the effect of season of blood sampling and type of surgery on the main variables. For all the analyses, P values less than or equal to 0.05 were considered as statistically significant. Findings: Serum 25(OH)D deficiency was identified in 52 (74.3%) of the patients. Patients with serum Vitamin D levels < 30 ng/ml had longer length of ICU stay than those with serum Vitamin D levels ≥ 30 ng/ml (7.8 ± 5.1 vs. 4.05 ± 2.12 days, P = 0.003). Although hospital mortality was more common in Vitamin D deficient patients than sufficient ones (25% in deficient group versus 22.2% in sufficient group), there was no significant difference regarding hospital mortality rate between the groups. Conclusion: Statistically significant association was found between low 25(OH)D level and increased length of ICU stay in critically ill surgical patients. It could be explained by favorable effects of Vitamin D on immune system functions, reducing tissue dysfunction, and risk of organ failure and overall complications. However, there was no correlation between serum Vitamin D level and patients' in-hospital mortality. Further, well-designed prospective clinical studies with adequate sample size are needed to evaluate correlation between serum Vitamin D level and mortality in critically ill patients.